Volume 2A: Turbomachinery 2015
DOI: 10.1115/gt2015-42474
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Aspirated Compressor Stator by Means of DoE

Abstract: This paper presents the design of an aspirated stator of a four-stage high-speed axial compressor. The aspiration of near-wall fluid at the suction side of the first stator is designed numerically by means of DoE (Design of Experiments). The design objective is a reduction or complete suppression of hub corner separation at off-design conditions. As operating point for the CFD-based design process, the last numerically stable operating point near the stall limit of the reference configuration at 80% of the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Siemann and Seume designed a compressor diffuser using DoE to see the effects of four parameters and their interactions on the blade efficiency [15].…”
Section: Introductionmentioning
confidence: 99%
“…Siemann and Seume designed a compressor diffuser using DoE to see the effects of four parameters and their interactions on the blade efficiency [15].…”
Section: Introductionmentioning
confidence: 99%
“…A 3D numerical simulation showed that the multistage aspirated compressor achieved a total pressure ratio of 6.03 at a tip speed of 370 m/s with an efficiency of 0.8636. Based on design of experiments correlation factors, Siemann and Seume 21 optimized the aspirated stator in a four-stage high-speed axial compressor, and the optimization result showed an increase in the overall isentropic efficiency of 1.3% to 0.9098, whereas the total pressure ratio increased by 0.08 to 2.08.…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, by introducing oscillating momentum coupled with flow instability, more efficient control effects could be obtained. 2 A majority of current researches about active separation control (both steady and periodic) in compressor cascades, such as synthetic jets, 3 plasma actuation, 4 boundary layer suction (BLS), [5][6][7][8][9] and jet flow 10 are based on different forms of momentum transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent work by Merchant et al, 6 a single aspirated compressor stage producing pressure ratio of 3.4 at the tip speed of 457.2 m/s with 3.5% inlet mass flow rate steadily aspirated was designed and validated. Following studies 5,[7][8][9] were dedicated to exploiting the potential of this method for significant impact on axial compressors.…”
Section: Introductionmentioning
confidence: 99%